Government efficiency and economic development in selected countries - Galooyek, Maryam Jafari (2016)
The financial crisis that lasted from 2007 to 2009 highlighted the inabilities of markets to manage macroeconomic variables. In addition, the inefficiency of free markets has led us to approve of government intervention. Nevertheless, it is necessary to remind ourselves that sometimes governments create fluctuations and make mistakes when developing policies in an economy. The recent economic crisis in the Eurozone gives reason to highlight the incompetence and inefficiency of the European governments who caused the situation to deteriorate. As a result, most experts believe that the recent economic crisis has been the crisis of Governments.Hence, most economists explain that to make development and positive progress,societies not only need a powerful government to achieve a better situation, but they also require a good government, as it is one of the most effective tools to reach the goals of countries. Although a good government is recognized and defined by different criteria, such as good people, good process, good accountability, good performance, and good standard, investigating all the aspects of good government is beyond our study’s purpose. Based on a theoretical background, we have concentrated on government efficiency as one of the primary requirements for defining a good government. However, it would be interesting to observe how the efficiency of governments could affect economic development progress.Accordingly, in the first step, we applied a Stochastic Frontier Analysis (SFA) model to estimate government efficiency by considering the factors that created inefficiency in 49 countries during the years between 1996 and 2013. The efficiency of central governments has been structured based on the Opportunity and Musgravian indicators. The SFA method is able to consider the explanatory variables that influence the level of inefficiency. In addition, the result of this research illustrates that government efficiency does not solely depend on the level of a country’s income.The second objective concerns the effects of government efficiency on human development as a proxy to evelopment. To this aim, we have listed 49 countries in three income groups: high, middle, and low income, over the period spanning 1996 to 2013. The positive relationship between government efficiency and the economic development process, by assuming the different level of income, has been represented by using the dynamic panel data method, known as System GMM.Finally, regarding the dawn of the crisis in developed countries, especially those in Europe, happened when governments concentrated on fulfilling their financial policy package through the injection of capital and liquidity. This hasty decision was a catalyst to sparking the difficulties of repaying their debt. Thus, the impact of the inefficiency of governments on government debt has been analyzed for 6 selected European countries using the Pooled Mean Group (PMG) model between 1996 and 2013. The estimation of this relationship has subsequently found a positive link between government inefficiency in the economic responsibility of government and government debt, which was intensified in the economic crisis. On the other hand,the role of government in an economy was not rejected, but rather government inefficiency has been introduced as an obstacle to the economic development process.